Implementasi Metode ANP-PROMETHEE Untuk Pemilihan Supplier (Studi Kasus PT. Lamongan Marine Industry) - Wicaksono, Mahad; Surarso, Bayu; Farikhin, Farikhin (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
The selection of suppliers is essential to minimize the cost of procuring raw materials for production. This research is important to do in order to increase company profits and ensure the smooth production process. This study aims to select suppliers of shipbuilding raw materials of PT. LMI based on the best ranking order using the ANP-PROMETHEE method implemented in a decision support system. The variables used are 16 sub criteria and 6 alternatives. The ANP-PROMETHEE method is used because of its advantages in handling multi-criteria assessment based on subjective assumptions from decision makers. Stages of the study began with the ANP method to get the importance of weight then proceed to the calculation with the PROMETHEE method to get an alternative ranking. The results of this study is an application as a Decision Support System (DSS) that can help make supplier selection based on predetermined criteria. From the results of the study it was concluded that the ANP-PROMETHEE method can be implemented and is the right solution for supplier selection, ANP handles the problem of multiple objective decision making so that objectivity is maintained, while PROMETHEE handles the multi attribute decision making problem. Other conclusions are obtained that the PROMETHEE calculation has a more significant influence in determining the final outcome of an alternative ranking than the ANP. An input of ANP value is needed with a long number interval so that the results of the calculation of the Consistency Ratio (CR) approach the CR threshold (0.1) so that the ANP has a significant influence in determining the final outcome of an alternative ranking. The CR number that was tested was 0.0629 and proved unable to change the alternative ranking final results, when the CR number that was tested was 0.0993, it was proven to be able to change the alternative ranking final results.